Assessing competency in neonatal resuscitation among medical students, interns and postgraduate students: a study from a tertiary care hospital in North India - Gautam, Piyush; Sharma, Nivedita (International Journal of Research in Medical Sciences, 2022)
Background: Birth asphyxia is a leading cause of neonatal mortality in India and many newborns suffer asphyxia due to lack of resuscitation skills among doctors. Fresh medical graduates get posted in the peripheral health centres where they handle all emergencies, including birth asphyxia. The aim of the study was to ascertain competency in neonatal resuscitation among medical students, especially interns who, within the next few months would be handling such babies. Methods: Final year medical students (30), interns (30), and first and second year pediatrics postgraduate students (9) were included. They were assessed for knowledge by a questionnaire of 15 multiple choice questions (MCQ’s), with a pass percentage of 73% (11/15). Practical skills were assessed by 4 assessors on a manikin using a skills assessment checklist of 11 skill items. Results: The percentage of medical students, interns and postgraduates passing the theory test was zero, 15% and 33% respectively. In the skills assessment, it was found that bag and mask ventilation, the single most important and effective step in resuscitation was performed by only 17% MBBS students and 20% interns respectively. Though most postgraduates could perform majority of the skills, 44% did drying before suctioning which is a wrong sequence. Conclusions: Medical students and interns are not competent in neonatal resuscitation. Even postgraduates, in absence of a structured training course are likely to fall short of the desired competency. So, there is an urgent need to train our medical students and interns so that as fresh graduates, they are competent to resuscitate asphyxiated newborns.